Assay of the Factors Affecting Student‟s Success in Teaching - Ozkan, Timucin; Tokel, Aytac; Gunay, Tugrul (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to reveal the factors that affect the success of students in teaching. Questionnaire prepared for the purpose was practiced a total of 317 students who were selected from the 6th, 7th and 8th grade students, including 167 male and 150 female students, were educated in Cumhuriyet, Lefkoşa Turk and Namık Kemal high schools in TRNC in 2017-2018 academic year. Used data collection tool is, the questionnaire titled “Assay of the Factors Affecting Students' Success in Teaching” which is taken from a doctoral thesis entitled “Factors Affecting Student Achievement in Primary School Religious Culture and Moral Education Course.” In the study, 31 item Likert and teacher attitudes scale was used. The method of this study is conducted in a relational screening model to examine the change of quantitative research method. As a conclusion, there were no significant differences in the demographic characteristics except Mann-Whitney U test outputs of the Turkish lesson attitudes according to the male-female situation and the total lesson attitudes of the students compared to the total teacher attitudes according to the non-parametric correlations test.